The Correlation between the Culture of Islamic Boarding Schools and Student Behavior - Lindawati, Yustika Irfani; Siregar, Herlina; Indriyani, Lemi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The focus of the research is to analyze the correlation between the culture of the Salaf Islamic Boarding School and the student behavior in Wewengkon Citorek. The approach used in this research was quantitative research with correlation type of research. Data collection used a questionnaire. Primary data is collected through questionnaires that are distributed directly to respondents. Secondary data obtained from the library, previous research reports, monthly reports of Islamic boarding schools, recapitulation condition of Islamic boarding schools, as well as other supporting data in section administration. Data analysis techniques include validity testing, reliability testing, and hypothesis testing with test criteria. If ρ empirical > ρ table, then reject H0 and accept H1. Likewise, if empirical ρ < ρ table, then reject H1 and accept H0. The population of this study consisted of 1513 students of Wewengkon Citorek from 24 Islamic boarding schools, and the criteria for male students were 1019 and female students were 494. Those samples were counted by a random sampling technique that used the table by Isaac and Michael for an error rate of 5%. Sampling in this study was carried out by the technique of disproportionate stratified random sampling. The total population is 1513, consisting of 1019 male students and 494 female students, so the sample calculation results obtained as many as 307 respondents. The distribution was for male students, as many as 207 respondents, and female students, as many as 100 respondents. The results of this study were as follows: Based on the calculation of the SPSS software version 25, it shows that the calculation of the normality test of the data is normally distributed because the significance value is 0.200, or it can be said that 0.200 ≥ 0.05. The linearity test calculation shows a linear pattern because the significance value is 0.298, or it can be said that 0.298 ≥ 0.05. Based on the correlation test of the Salaf Islamic boarding school culture using the product moment correlation technique, the value is 0.421. It can be said that the null hypothesis (Ho) is rejected, and the research hypothesis (H1) is accepted. The rxy value that has been obtained is 0.421, and it is located between 0.40 – 0.59 in the product-moment correlation index. The results of testing the hypothesis show that there is a positive relationship between the culture of the Salaf Islamic boarding school (X) and the behavior of students (Y) on the strength of the relationship that is moderate or sufficient.